Neighborhood environment associations with cognitive function and structural brain measures in older African Americans - Dima L. Chaar; Le Tu; Kari Moore; Jiacong Du; Lauren A Opsasnick; Scott M Ratliff; Thomas H Mosley; Sharon L. R. Kardia; Wei Zhao; Xiang Zhou; Ana V Diez Roux; Fazlay S Faruque; et al. (BMC Medicine)
Abstract Background Since older adults spend significant time in their neighborhood environment, environmental factors such as neighborhood socioeconomic disadvantage, high racial segregation, low healthy food availability, low access to recreation, and minimal social engagement may have adverse effects on cognitive function and increase susceptibility to dementia. DNA methylation, which is associated with neighborhood characteristics as well as cognitive function and white matter hyperintensity (WMH), may act as a mediator between neighborhood characteristics and neurocognitive outcomes. Methods In this study, we examined whether DNA methylation in peripheral blood leukocytes mediates the relationship between neighborhood characteristics and cognitive function (N = 542) or WMH (N = 466) in older African American (AA) participants without preliminary evidence of dementia from the Genetic Epidemiology Network of Arteriopathy (GENOA). Results For a 1-mile buffer around a participant’s residence, each additional fast food destination or unfavorable food store with alcohol per square mile was nominally associated with a 0.05 (95%CI: 0.01, 0.09) and a 0.04 (0.00, 0.08) second improvement in visual conceptual tracking score, respectively. Also, each additional alcohol drinking place per square mile was nominally associated with a 0.62 (0.05, 1.19) word increase in delayed recall score, indicating better memory function (all p < 0.05). Neighborhood characteristics were not associated with WMH. We did not find evidence that DNA methylation mediates the observed associations between neighborhood characteristics and cognitive function. Conclusions The presence of fast food destinations and unfavorable food stores with alcohol was associated cognitive measures, possibly due to greater social interaction provided in these venues. However, replication of these findings is necessary. Further examination of the potential pathways between the neighborhood environment and cognitive function/WMH may allow the development of potential behavioral, infrastructural, and pharmaceutical interventions to facilitate aging in place and healthy brain aging in older adults, especially in marginal populations that are most at risk.